Automatic alignment of solar disk images and accurate determination of heliographic coordinates sunspot analysis with PySDIA - Grangeiro, Cicero Dário; Duarte, Tharcísyo Sá e Sousa; Costa, Jefferson Soares da; Coelho, Hugo Rodrigues (Cadernos de Astronomia, 2024)
This work introduces PySDIA (Python Solar Disc Image Alignment), an automated Python code for image alignment and rotational correction of solar disc images captured with small aperture telescopes. We have been applied PySDIA to a set of 101 self-obtained images spanning November 8, 2022 to December 4, 2023, to characterize and extract heliographic coordinates for 250 sunspots. To validate our results, we compared our data with SDO measurements extracted using HelioViewer v2.2 software. PySDIA effectively aligned and rotated our images, achieving excellent correlation between our sunspot coordinates and those from SDO. Our results demonstrate that precise sunspot coordinate measurements can be obtained over time using readily available equipment, enabling independent contributions to sunspot records and studies.
Keywords: small aperture telescope; sunspots; heliographic coordinates; PySDIA